Industrial assembly - Nof, Shimon Y. (Chapman & Hall, 1997)
Industrial Assembly is a rapidly changing field with significant importance in production. This book is the first of its kind to combine technology, design, methods, and planning and control models of assembly operations and systems. With the increasing importance of assembly in industry and of simultaneous engineering approaches, this timely publication provides: comprehensive coverage of technological, engineering, and management aspects of this field; multi-disciplinary approaches to rationalization of assembly operations and systems; explanation of qualitative models, information technologies, and design techniques, which have been practised effectively in industrial assembly; as well as theoretical foundations and emerging trends that shape the future of assembly.